2007
DOI: 10.1088/1741-2560/4/4/003
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of upper limb muscle activity from motor cortical discharge during reaching

Abstract: Movement representation by the motor cortex (M1) has been a theoretical interest for many years, but in the past several years it has become a more practical question, with the advent of the brainmachine interface. An increasing number of groups have demonstrated the ability to predict a variety of kinematic signals on the basis of M1 recordings and to use these predictions to control the movement of a cursor or robotic limb. We, on the other hand, have undertaken the prediction of myoelectric (EMG) signals re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 36 publications
3
83
0
1
Order By: Relevance
“…A direct comparison of end point kinematics and grip force found the latter to be predicted dramatically better (Carmena et al 2003), although EMG was predicted less accurately in that study. However, two other studies achieved predictions of the EMG measured from wrist muscles during isometric contractions with R 2 in the 0.7-0.8 range (Oby et al 2010;Pohlmeyer et al 2007b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A direct comparison of end point kinematics and grip force found the latter to be predicted dramatically better (Carmena et al 2003), although EMG was predicted less accurately in that study. However, two other studies achieved predictions of the EMG measured from wrist muscles during isometric contractions with R 2 in the 0.7-0.8 range (Oby et al 2010;Pohlmeyer et al 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that caudal M1, with its increased tactile responsiveness, represents a newer cortical system that has evolved to provide the increased dexterity of humans and more advanced primates (Nakajima et al 2000;Preston 1978a, 1978b). Attempts to decode muscle activity related to the wrist and hand may well profit from recordings made in caudal M1 (Oby et al 2010;Pohlmeyer et al 2007bPohlmeyer et al , 2009). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a closely related project, we have demonstrated that recordings from similar UEAs implanted in the primary motor cortex of monkeys can provide accurate information about muscle activity during normal or intended movement (Pohlmeyer et al 2007). The information can be used to restore simple voluntary movement to monkeys during peripheral nerve block, used as a temporary paralysis model of SCI.…”
Section: Brain-controlled Activation Of Motor Nerve Fibers and Behaviormentioning
confidence: 99%